Quality of life of Brazilian vegetarians measured by the WHOQOL-BREF : influence of type of diet, motivation and sociodemographic data - Hargreaves, Shila Minari (2021)
This study aimed to evaluate the general quality of life (QoL) of Brazilian vegetarians. A cross-sectional study was conducted with Brazilian vegetarian adults (18 years old and above). Individuals were recruited to participate in a nationwide online survey that comprised the WHOQOL-BREF as well as sociodemographic and characterization questions related to vegetarianism. The WHOQOL-BREF is composed of 24 items which are divided into four domains (domain 1: physical health; domain 2: psychological well-being; domain 3: social relationships; and domain 4: environment), plus two general items which were analyzed separately, totaling 26 items. The answers from the questionnaire were converted into scores with a 0–100 scale range, with separate analyses for each domain. Results were compared among groups based on the different characteristics of the vegetarian population. A total of 4375 individuals completed the survey. General average score results were 74.67 (domain 1), 66.71 (domain 2), 63.66 (domain 3) and 65.76 (domain 4). Vegans showed better scores when compared to the other vegetarians, except in domain four, where the statistical difference was observed only for semi-vegetarians (lower score). Individuals adopting a vegetarian diet for longer (>1 year) showed better results for domains one and two, with no difference for the other domains. Having close people also adopting a vegetarian diet positively influenced the results for all domains. On the other hand, it was not possible to distinguish any clear influence of the motivation for adopting a vegetarian diet on the scores’ results. Adopting a vegetarian diet does not have detrimental effects on one’s QoL. In fact, the more plant-based the diet, and the longer it was adopted, the better the results were.